Peran Kewirausahaan Dan Inovasi Dalam Kemajuan Ekonomi Indonesia - Nova, Mellynda Az Zahra (Maliki Interdisciplinary Journal, 2025)
Indonesia as a developing country faces various economic challenges, including high unemployment rates and low entrepreneurship rates. Entrepreneurship plays an important role in increasing economic progress through job creation, innovation, and reducing unemployment. Although the potential for entrepreneurship is great, challenges such as limited access to capital, infrastructure, and regulations remain major obstacles. This literature-based analysis method emphasizes the importance of entrepreneurship, as well as government efforts to support entrepreneurial growth through innovative policies and access to financing. The results of this study indicate that with the right policies, entrepreneurship can be a major driver of sustainable growth and progress of the Indonesian economy. Entrepreneurship is also one of the determinants in creating a prosperous society and country.